Recycled gypsum block: development and performance - Santana, Clóvis Veloso; Póvoas, Yêda Vieira; Silva, Deborah Grasielly Cipriano da; Miranda Neto, Francisco de Assis (Ambiente Construído, 2019)
<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: IT; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="IT">The gypsum plaster waste is still faced a serious economic and environmental problem. Considering the high volume and the destination often inadequate. Intending to provide a mitigating alternative, this research intends to develop blocks that incorporate the industrial gypsum plaster waste through reverse logistics. For this, a physic-chemical recycling process of gypsum plaster waste was carried out on an industrial scale and the developed material was characterized in anhydrous and fresh state. Then, blocks were made with the recycled material and characterized according to NBR 16495 (ABNT, 2016). After its characterization, the material was evaluated for its mechanical performance when used in walls, regarding the tests of suspended vertical loads and hard and soft body impact, according to the guidelines included in the performance standard NBR 15575-4 (ABNT, 2013). The walls constituted with the developed material showed satisfactory performance, having, in some cases, presented superior performance in comparison to the conventional walls of gypsum blocks, according to results presented by the Technical Assessments Document - DATEC nº 27 (2015). Finally, small walls of the recycled gypsum block and gypsum glue were elaborated to verify the compressive behavior. Regarding these verifications, it was noticed that the small walls obtained good resistive capacity.